Management of Broiler Chicken Maintenance with a Semi-Closed Cage System in the Cages of Partner Breeders PT. Pitik Digital Indonesia - Nur Hanif, Fitra; Sudrajat, Deden; Wahyuni, Dewi; Karya, Dede (Jurnal Agrosci, 2024)
Indonesia's growing population continues to increase the need for animal protein, including meat, milk, and eggs. Public awareness of the importance of animal protein in nutrition is increasing. In this context, meat becomes one of the most consumed sources of animal protein, because in addition to its good taste it is also due to its high nutritional content. Field Work Lectures (MPAs) are conducted to apply theory in field practice, especially in broiler chicken rearing management. MPA activities are carried out in the cages of partner breeders of PT. Pitik Digital Indonesia in West Java, which includes primary and secondary data collection and implementation of maintenance management standards. The productivity project results of the Farming program show increased efficiency in achieving the expected chicken weight, through improvements in facilities and infrastructure as well as the use of applications that facilitate maintenance. Broiler rearing management involves several stages, including cage preparation, feeding, maintenance, to the harvesting process. The cage used has a semi-closed system and faces from North to South. The breed of chickens raised is broiler chickens of the Cobb strain. Although the performance index shows good performance, improvements in biosecurity and sanitation of cages are needed to reduce chicken mortality and disease risk.